Liver function effects of SGLT2 inhibitor and GLP‐1 receptor agonist combination treatment in patients with type 2 diabetes (post hoc analysis of RECAP study) - Daisuke Tsuriya; Kazuo Kobayashi; Kei Takeshita; Takuya Hashimoto; Moritsugu Kimura; Yoshimi Muta; Hisashi Yokomizo; Yuichi Takashi; Shunichiro Tsukamoto; Kouichi Tamura; Keizo Kanasaki; Daiji Kawanami; et al. (Journal of Diabetes Investigation, 2025)
ABSTRACT Aim The favor effect on liver disease by odium‐glucose cotransporter inhibitor (SGLT2i) and GLP‐1 receptor agonist (GLP1Ra) was reported; however, the effect of the combination treatment of these drugs was not well known. Methods We retrospectively analyzed data for 643 patients with type 2 diabetes receiving SGLT2i + GLP1Ra combination treatment for at least 1 year (331 and 312 patients in the GLP1Ra‐ and SGLT2i‐preceding groups, respectively). Propensity score (PS) matching was used to compare the effects of the preceding drugs on liver function. Results The mean AST and ALT values at baseline, at the initiation of combination treatment, and at final observation were 29.8 ± 20.0 and 37.7 ± 29.5, 28.7 ± 17.3 and 35.3 ± 6.0, 26.0 ± 14.6 and 30.1 ± 21.6 IU/L, respectively, indicative of significant improvements in liver function (P < 0.001). Conversely, significant progress in the fibrosis‐4 (FIB‐4) index category was observed even after the combination treatment (P = 0.03). Subgroup analysis revealed that a significant decrease in ALT was observed only in patients with a baseline ALT ≥30 IU/L after the combination treatment (P = 0.005). Improvement of the FIB‐4 index category was observed in patients in the baseline FIB‐4 index ≥2.6 group and in the 1.3 ≤FIB‐4 index <2.6 group (46% and 19%, respectively). The matched model showed no significant differences in liver function after combination treatment between the SGLT2i‐ and GLP1Ra‐preceding groups. Conclusions SGLT2i + GLP1Ra combination treatment significantly improved liver dysfunction and prevented the progression of FIB‐4 index category among patients with an FIB‐4 index ≥1.3.